Coffee, its roasted form, and their residues cause birth failure and shorten lifespan in dengue vectors - Hamady, Dieng; Salbiah, Ellias; Tomomitsu, Satho; Abu Hassan, Ahmad; Tonga, Noweg (Springer Verlag, 2017)
In dengue mosquitoes, successful embryonic development and long lifespan are key determinants for the persistence of both virus and vector. Therefore, targeting the egg stage and vector lifespan would be expected to have greater impacts than larvicides or adulticides, both strategies that have lost effectiveness due to the development of resistance. Therefore, there is now a pressing need to find novel chemical means of vector control. Coffee contains many chemicals, and its waste, which has become a growing environmental concern, is as rich in toxicants as the green coffee beans; these chemicals do not have a history of resistance in insects, but some are lost in the roasting process. We examined whether exposure to coffee during embryonic development could alter larval eclosion and lifespan of dengue vectors. A series of bioassays with different coffee forms and their residues indicated that larval eclosion responses of Aedes albopictus and Ae. aegypti were appreciably lower when embryonic maturation occurred in environments containing coffee, especially roasted coffee crude extract (RCC). In addition, the lifespan of adults derived from eggs that hatched successfully in a coffee milieu was reduced, but this effect was less pronounced with roasted and green coffee extracts (RCU and GCU, respectively). Taken together, these findings suggested that coffee and its residues have embryocidal activities with impacts that are carried over onto the adult lifespan of dengue vectors. These effects may significantly reduce the vectorial capacity of these insects. Reutilizing coffee waste in vector control may also represent a realistic solution to the issues associated with its pollution.